Publisher Correction: The global distribution of tetrapods reveals a need for targeted reptile conservation. Issue 11 (November 2017) - Roll, Uri; Feldman, Anat; Novosolov, Maria; Allison, Allen; Bauer, Aaron; Bernard, Rodolphe; Böhm, Monika; Castro-Herrera, Fernando; Chirio, Laurent; Collen, Ben; Colli, Guarino; Dabool, Lital; et al.
In this Article originally published, owing to a technical error, the author 'Laurent Chirio' was mistakenly designated as a corresponding author in the HTML version, the PDF was correct. This error has now been corrected in the HTML version. Further, in Supplementary Table 3, the authors misspelt the surname of 'Danny Meirte'; this file has now been replaced.